A memoir and reflection: knowledge and an evolutionary theory of the multinational firm 10 years later - Kogut, B; Zander, U (Journal of International Business Studies, 2003)
The production of the 1993 article awarded the JIBS Decade Award was written during a time when ideas regarding knowledge and the international expansion of the firm confronted a hostile audience. The sources of these ideas were directly related in Winter's and Roger's prior work, but also to a broader literature on ‘category errors’ and technology transfer. The theory of the firm as a social community is a distinctly sociological theory and, though sharing many key ideas with the resource-based view that developed at the same time, is deeply opposed to engineering conceptions of firms as Lego-modular pieces that can be easily shifted, bought, and sold. We describe our individual biographies and the subsequent intellectual development of the concepts in our article.